2014
DOI: 10.3928/00989134-20140905-01
|View full text |Cite
|
Sign up to set email alerts
|

Knowing Versus Doing: Education and Training Needs of Staff in a Chronic Care Hospital Unit for Individuals With Dementia

Abstract: ARTICLEHOW TO OBTAIN CONTACT HOURS BY READING THIS ARTICLE Instructions 1.2 contact hours will be awarded by Villanova University College of Nursing upon successful completion of this activity. A contact hour is a unit of measurement that denotes 60 minutes of an organized learning activity. This is a learner-based activity. Villanova University College of Nursing does not require submission of your answers to the quiz. A contact hour certifi cate will be awarded once you register, pay the registration fee, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 28 publications
3
51
1
1
Order By: Relevance
“…Sixteen studies were quantitative, one study was qualitative, and two studies utilized mixed methods . The qualitative study used content analysis to assess perspectives after implementing a training video.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies were quantitative, one study was qualitative, and two studies utilized mixed methods . The qualitative study used content analysis to assess perspectives after implementing a training video.…”
Section: Resultsmentioning
confidence: 99%
“…The qualitative study used content analysis to assess perspectives after implementing a training video. Among the quantitative studies, seven were interventional, seven were descriptive, one was a randomized controlled trial, and one was cross‐sectional …”
Section: Resultsmentioning
confidence: 99%
“…NAs and AHWs voice considerable frustration about caring for individuals with dementia (Hynninen, Saarnio, & Isola, 2015; Marx et al, 2014), and have indicated a need for more information and skills related to actual care situations, behavioral management, safety of individuals with dementia, activities with individuals with cognitive impairment, and coping skills. They have also indicated feeling disrespected by families of individuals with dementia (Marx et al, 2014).…”
mentioning
confidence: 99%
“…They have also indicated feeling disrespected by families of individuals with dementia (Marx et al, 2014). A recent meta-synthesis of qualitative research identified over-arching themes related to NAs’/AHWs’ challenges when caring for hospitalized individuals with dementia: Overcoming Uncertainty When Delivering Care, Inequality in the Quality of Care Provided to Individuals With Dementia, Recognizing the Benefits of Person-Centered Care but Not Being Able to Deliver it Due to Constraints of the Environmental and Wider Organizational Context , and Need for Training (Turner, Eccles, Elvish, Simpson, & Keady, 2015).…”
mentioning
confidence: 99%
“…Families are typically on their own to learn about behaviors and their management [13,14]. While some caregiver interventions show reductions in behavioral occurrences and caregiver distress, they are time-consuming, labor-intensive and provide decision support and strategies for a limited time [1517].…”
Section: Introductionmentioning
confidence: 99%